Preliminary design and analysis of a sodium-cooled, graphite-moderated TRISO-matrix reactor (SGTR) using OpenMC modeling - Burns, Killian (My University, 2025)
A pin cell of a sodium-cooled, graphite-moderated, thermal TRISO reactor (SGTR) is simulated and analyzed in OpenMC, an open-source Monte Carlo modeling program. The thermal properties, depletion characteristics, and power production capacity for a single pin are detailed and studied in this report, with extrapolation to a reactor comprised of 700 fuel rods. The assembled reactor core is designed to produce 100 MWth, maintains a positive reactivity through the 60th month of operation, and operates at a burnup of 79.5 (GW_d)/(MTU ) during this period. The fuel pin is simulated using a homogenous fuel material mix to approximate varying size TRISO beads embedded in a zirconium matrix at a packing fraction of 0.55. The fuel pin measures 400 cm in length with a radius of 3.6 cm, surrounded by a coolant channel of width 1.314 cm and a 20 cm pitch of graphite moderator between hexagonally arranged pins, and thin layers of stainless-steel cladding line the coolant channel. The reactor design requires 100 fuel pins arrayed among each of its 7 hexagonal subassemblies, such that each pin generates 142.9 kW at operational power. The SGTR reactor yields a core power density of 57.32 MW/m^3 with an initial heavy metal loading of 2263.8 kg Uranium.
Keywords: Small modular reactor (SMR); Tri-structural Isotropic (TRISO) fuel; Graphite moderator; Sodium coolant; OpenMC